2008
DOI: 10.2320/matertrans.mra2008085
|View full text |Cite
|
Sign up to set email alerts
|

Design of Cascaded Oxide Thermoelectric Generator

Abstract: This paper describes the design of two-and three-stage cascaded oxide thermoelectric generators (TEGs) for high-temperature heat recovery using reported data to optimize energy conversion efficiency. We used the general intermetallic compounds Bi 2 (Se,Te) 3 and (Bi,Sb) 2 Te 3 for the low-temperature stages and oxides of TiO 1:1 , La-doped SrTiO 3 , Na x Co 2 O 4 , and Al-doped ZnO for the higher-temperature stages. A two-stage TEG with TiO 1:1 as the p-type material and La-doped SrTiO 3 as the n-type material… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 26 publications
(26 reference statements)
0
9
0
Order By: Relevance
“…It should be noted that at present there is a high interest to titanium monoxide as a material for cascaded oxide thermoelectric generators [21] due to its unique thermoelectric properties [22]. Additionally, titanium monoxide can be used in microelectronics as a diffusion barrier against the inter-diffusion of Al and Si [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that at present there is a high interest to titanium monoxide as a material for cascaded oxide thermoelectric generators [21] due to its unique thermoelectric properties [22]. Additionally, titanium monoxide can be used in microelectronics as a diffusion barrier against the inter-diffusion of Al and Si [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…The performance can be enhanced by stacking several TE modules (so-called cascade modules) [6][7][8]. The cascade TE generation efficiency can be increased by using materials suitable for the working temperature range.…”
Section: Temperature (K)mentioning
confidence: 99%
“…In a practical module construction, Zhang et al [7] indicated that cascade TE generators using TE oxides have a high potential for heat recovery from hightemperature waste. Funahashi [8] fabricated cascade modules consisting of oxide and Bi 2 Te 3 modules and indicated experimentally that cascade structures are effective for high efficiency.…”
Section: Temperature (K)mentioning
confidence: 99%
“…For each form of waste heat, suitable recovering methods were proposed. For example, thermoelectric conversion for wall heat loss, [6][7][8][9] pre-heating of materials and steam generation for fluid sensible heat and radiation, etc. One of the attracting technologies is latent heat storage [10][11][12][13][14] that once stores thermal energy as latent heat of melting and then supplies it to the distant place with time-shift and flattened temperature level.…”
Section: Introductionmentioning
confidence: 99%